Durable Balance: Informed Reform and Energy Decision-Making in Canada - Cleland, Michael; Gattinger, Monica; Beck, Marisa; Aguirre, Rafael (Université d'Ottawa | University of Ottawa, 2018)
In 2015, the University of Ottawa launched the Positive Energy initiative. The mandate of the first three years of Positive Energy has been to strengthen public confidence in Canadian energy policy, regulation and decision-making through evidence-based research and analysis, engagement and recommendations for action. This report marks the conclusion of the first three years of Positive Energy, summing up what was undertaken and achieved, what was learned that may inform the actions of others, and what remains to be done as Canada looks to grapple with ever-growing strains on its energy economy and decision-making system.
Keywords: Energy Policy; Energy Regulation; Canada; Public Confidence; Climate Change; Positive Energy